β-CASP proteins removing RNA polymerase from DNA: when a torpedo is needed to shoot a sitting duck - Wiedermannová, Jana; Krásný, Libor (Nucleic acids research, 2021)
During the first step of gene expression, RNA polymerase (RNAP) engages DNA to transcribe RNA, forming highly stable complexes. These complexes need to be dissociated at the end of transcription units or when RNAP stalls during elongation and becomes an obstacle ('sitting duck') to further transcription or replication. In this review, we first outline the mechanisms involved in these processes. Then, we explore in detail the torpedo mechanism whereby a 5'-3' RNA exonuclease (torpedo) latches itself onto the 5' end of RNA protruding from RNAP, degrades it and upon contact with RNAP, induces dissociation of the complex. This mechanism, originally described in Eukaryotes and executed by Xrn-type 5'-3' exonucleases, was recently found in Bacteria and Archaea, mediated by β-CASP family exonucleases. We discuss the mechanistic aspects of this process across the three kingdoms of life and conclude that 5'-3' exoribonucleases (β-CASP and Xrn families) involved in the ancient torpedo mechanism have emerged at least twice during evolution.
Keywords: exoribonukleasy; Exoribonucleases; Protein Binding; Transcription, Genetic; DNA; DNA-Directed RNA Polymerases; Eukaryota; genetická transkripce; vazba proteinů; DNA řízené RNA-polymerasy; Bacteria; Archaea